Massive hemobilia in a cirrhosis patient after percutaneous liver biopsy - Cheng, Qian; Li, Yue; Luo, Xiaoping; Gong, Jianping (International Surgery Journal, 2016)
Hemobilia is commonly seen in clinic after liver injury or other diseases, but it is uncommonly secondary to percutaneous liver biopsy, especially leading to significant hemorrhage. We reported a case that a patient with post hepatitis C cirrhosis has received percutaneous liver biopsy at our hospital. After that, the patient suffered from discontinuous abdominal pain and jaundice which were caused by the obstruction of blood clots due to hemobilia, but there was no performance of upper gastrointestinal bleeding. Not until the symptoms of hemorrhagic shock emerged did the diagnosis of hemobilia was confirmed. Urgently surgical exploration eliminated blood clots in biliary tract relieving biliary obstruction. And then the hemorrhage was restrained by selective transcatheter arterial embolization. Pseudoaneurysm and arterioportal fistula were also found by hepatic arteriography. We learn from this case that rational choice of treatments is of importance, whether surgery, arterial embolization, conservative therapy or the combination of them, which mainly rests on the situation.